Matter, meaning and semiotics - O’Halloran, Kay L (Visual communication (London, England), 2023)
We inhabit two worlds – the world of matter and the world of meaning (see Halliday, ‘On matter and meaning: The two realms of human experience, 2005). In this article, these two worlds and the physical, biological, social and semiotic systems that connect them are investigated. In this respect, semiotic systems are the most complex because they involve physical systems (the material sign), biological systems (human beings), social systems (society and culture) and meaning itself. Semiotic frameworks need to take into account these various dimensions as changes in one system reverberate across the meta-system as a whole. With this in mind, the interplay between material and semiotic worlds from a social semiotic perspective, are explored with a focus on meaning and its significance in relation to human existence. Using examples from various industrial ages, the article explores how semiotic resources (in this case, in mathematics, science and computer programming languages) are organized to structure reality in specific ways, and how semiotic combinations and the technologies arising from those constructions have changed the course of human history. In this discussion, attention is paid to the role of visual communication, both in terms of visual semiotic resources (e.g. graphs, digital images) and visual aspects of multimodal texts. It thus becomes evident that the functionalities of any one semiotic resource (including language) must be viewed in relation to its collective co-deployment with other semiotic resources. Lastly, the author examines semiosis in the digital age and considers the social implications of the current digital ecosystem. In doing so, she conceptualizes digital technologies as a one-way mirror where members of society use digital media for every facet of their lives while being watched, analysed and manipulated by those who have designed and own the digital platforms. It is apparent that semiotics has a major role to play in terms of design, policymaking and activism around future digital technologies.